PENGARUH LINGKUNGAN DAN TEKNIK BUDIDAYA TERHADAP EP I DEMI PENYAKIT VASCULAR STREAK DIEBACK (VSD) PADA TANAMAN KAKAO / Agronomical Practices and Environmental Effect to The Epidemics of Vascular Streak Dieback (VSD) Disease of Cocoa - nFN Khaerati; Suryo Wiyono; Efi Toding Tondok (Jurnal Penelitian Tanaman Industri, 2016)
Vascular Streak Dieback (VSD) in cocoa caused by Oncobasidium theobromae. This is one of the important disease of cocoa in the world, including Indonesia. The knowledge on environmental effect and agronomical practices to the epidemics of VSD disease of cocoa, is important to control the diseases. The objectives of this research were to investigate environmental effect and agronomical practices to the epidemic VSD disease of cacao. The study was conducted on February to August 2014 in the three sub districts namely Tinondo (≥ 700 m asl), Mowewe (300-400 m asl) and Lambandia (≤ 100 m asl) East Kolaka Regency, South East Sulawesi. The study was carried out by colleting primary data included agronomical practices, the measurement of VSD disease severity in the field and soil nutrient, as well as secondary data. The results of this research showed that the environment and agronomical practices gave an effect to the epidemics VSD disease. Monoculture plantation had higher severity than mixed garden of cocoa. More condense the canopy of cocoa, more severe the VSD disease. More near the location of cacao plants to the river, more humid the enviroment and more severe the desease. Potassium deficiency in plants will cause susceptible to the disease, the high levels of Mg may limit K and Zn uptake at the soil. Recommendation for reducing VSD disease severity on cocoa plantations are cropping systems mixed with other plants, prunning, reducing the use of insecticides and herbicides, and do not plant the cocoa near to the river.Keywords: cacao, disease, epidemic, Oncobasidium theobromae